Label-Free Cross-Priming Amplification Coupled With Endonuclease Restriction and Nanoparticles-Based Biosensor for Simultaneous Detection of Nucleic Acids and Prevention of Carryover Contamination - Wang, Yi; Sun, Lin; Li, Jie-qiong; Wang, Ze-ming; Jiao, Wei-wei; Xiao, Jing; Shen, Chen; Xu, Fang; Qi, Hui; Wang, Yong-hong; Guo, Ya-jie; Shen, A-dong (Frontiers in Chemistry, 2019)
Here, we reported on a label free cross-priming amplification (CPA) scheme that utilized endonuclease restrict for simultaneous detection of nucleic acids and elimination of carryover contamination. Reaction mixtures were detected in a nanoparticle-based lateral flow biosensor (LFB). The assay exhibited attractive traits in that it did not require the use of labeled primers or labeled probes, and thus, the technique could prevent undesired results arising from unwanted hybridization between labeled primers or between a probe and labeled primer. Isothemral amplification and endonuclease restriction digestion were conducted in a single pot, and the use of a closed-tube amplification removed false-positive results due to contaminants. To validate the assay’s applicability, we employed the novel technique to detect the pathogen Staphylococcus aureus in pure cultures and artificial blood samples. The assay could detect target bacterium in pure culture with a 100 fg.μL-1 detection limit, and in spiked blood samples with a 700 cfu.mL-1 detection limit. The whole process, including sample procedure (20-min), CPA amplification (60-min), endonuclease digestion (10-min) and result reporting (within 2-min), could be finished within 95-min. As a poof-of-concept assay, the technique devised in the current report could be employed for detecting various other sequences if the specific CPA primers were available.